2001
DOI: 10.4049/jimmunol.167.10.5539
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Antigen-Driven Lymphocyte Recruitment to the Lung Is Diminished in the Absence of Urokinase-Type Plasminogen Activator (uPA) Receptor, but Is Independent of uPA

Abstract: The requirement for urokinase plasminogen activator (uPA) and uPA receptor (uPAR) in T lymphocyte migration is unknown. uPA−/− mice have fewer pulmonary lymphocytes in response to certain infections, but its unknown whether this is due to diminished recruitment. Primed, recipient mice were IT inoculated with Ag. Three days later, fluorescently labeled lymphoblasts from background-matched control wild-type (WT), uPA−/−, or uPAR−/− donor mice were injected i.v., and their recruitment was determined. Approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…uPA also primes neutrophils for superoxide anion release (61), and uPAR expression is required for FMLP-dependent monocyte and granulocyte chemotaxis (45,46) and for neutrophil degranulation (62). Finally, uPA Ϫ/Ϫ and uPAR Ϫ/Ϫ mice show impaired neutrophil recruitment and susceptibility to bacterial infections (12)(13)(14). There is compelling evidence that mast cells and basophils are multifunctional effector cells in inflammation (63) and in host defense against bacteria, viruses and parasites (64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…uPA also primes neutrophils for superoxide anion release (61), and uPAR expression is required for FMLP-dependent monocyte and granulocyte chemotaxis (45,46) and for neutrophil degranulation (62). Finally, uPA Ϫ/Ϫ and uPAR Ϫ/Ϫ mice show impaired neutrophil recruitment and susceptibility to bacterial infections (12)(13)(14). There is compelling evidence that mast cells and basophils are multifunctional effector cells in inflammation (63) and in host defense against bacteria, viruses and parasites (64).…”
Section: Discussionmentioning
confidence: 99%
“…Migration of immune cells to tissue lesions is impaired in uPA Ϫ/Ϫ and uPAR Ϫ/Ϫ mice, resulting in impairment of host defenses, bacterial spread, and death (12)(13)(14). Chemotaxis of inflammatory cells stimulated by uPA in vitro and in vivo requires binding to uPAR (15)(16)(17) and the existence of a transmembrane adapter (15,18).…”
mentioning
confidence: 99%
“…Therefore, the lymphocyte subset percentages used in the following calculations were corrected for the number of Gr-1 ϩ cells contaminating the analysis gate. This type of adjustment was not performed in previous studies using this model system (13,14,16,18,19,24,25), because the light scatter characteristics of the flow cytometers used previously did not result in such contamination of the lymphocyte gates (24). The means of the replicate determinations for each subset were then used to calculate the absolute number of cells as detailed below.…”
Section: Flow Cytometry Analysis and Determination Of Absolute Lymphomentioning
confidence: 99%
“…SRBC (13)(14)(15)(16)(17)(18). Initial studies from our group and others showed that CD62E, CD62P, and VCAM are expressed on the lung microvasculature in sensitized mice after challenge with i.t.…”
mentioning
confidence: 99%
“…This model was chosen for its ability to induce an acute, self-limited inflammatory response with a clearly definable onset and well-established kinetics. Previous studies have proven this model system useful in defining the molecular mechanisms of lung leukocyte recruitment (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Following i.t.…”
mentioning
confidence: 99%